Normy prawne rachunkowości małych i średnich podmiotów gospodarczych a modele rachunkowości - Kaczmarczyk, Angelika (Legal Standards of Small and Medium Entities versus Accounting Models, 2007)
Small and Medium Entities are crucial economic determinants in Poland, in the European Union and in the whole world. The main aim of this article is an attempt to answer the following question: which countries, according to the accounting models, solve the problem of legal standards' creation for Small and Medium Entities?
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1158, s. 73-77